Therapeutic strategies to overcome ALK resistance in cancer - Friboulet, Luc (Cancer sensitizing agents for chemotherapy ;, 2021)
"Therapeutic Strategies to Overcome ALK Resistance in Cancer, Volume 13, presents current strategies to improve and prolong clinical benefit in ALK driven cancers. Most patients with ALK-driven cancer are sensitive to tyrosine kinase inhibitor (TKI) therapy, but resistance invariably develops. This book discusses topics such as structure and function of ALK, ALK rearranged lung cancer, resistance mechanisms to ALK TKI tumors, and novel therapeutic strategies to enhance crizotinib anti-tumor efficacy in ALCL. Additionally, it encompasses information on drug combinations to enhance ALK TKI anti-tumor efficacy in neuroblastoma and future perspectives in the field"--Publisher's description.